2017
DOI: 10.1111/jbi.12963
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast phylogeography of New Zealand Sophora trees (Fabaceae): extensive hybridization and widespread Last Glacial Maximum survival

Abstract: Aim To date, there have been few studies investigating the phylogeography of forest trees that are widely distributed in New Zealand. Our main objective was to examine the phylogeographic distribution of chloroplast DNA from New Zealand Sophora trees with respect to known biogeographical regions, proposed refugia and species boundaries. A second objective was to investigate the origins of the southern and Chatham Island populations of Sophora chathamica, which have been proposed to derive from Māori translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 60 publications
4
10
0
Order By: Relevance
“…However, S. molloyi appeared to be similar in assignment to S. microphylla , and S. godleyi comprised individuals with a range of assignment values as well as samples that appeared to be uniquely assigned to S. godleyi (pink samples in Figure 2 ). The close relationship between S. microphylla and S. molloyi is a similar result to that of Shepherd et al [ 10 ] who showed that in the southern North Island the two species share haplotype K and in the southern part of Cook Strait they share haplotype F. Sophora microphylla and S. molloyi are distinguished by their growth habit, leaf characters and ecological preferences as presented in the taxonomic revision [ 6 ].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…However, S. molloyi appeared to be similar in assignment to S. microphylla , and S. godleyi comprised individuals with a range of assignment values as well as samples that appeared to be uniquely assigned to S. godleyi (pink samples in Figure 2 ). The close relationship between S. microphylla and S. molloyi is a similar result to that of Shepherd et al [ 10 ] who showed that in the southern North Island the two species share haplotype K and in the southern part of Cook Strait they share haplotype F. Sophora microphylla and S. molloyi are distinguished by their growth habit, leaf characters and ecological preferences as presented in the taxonomic revision [ 6 ].…”
Section: Discussionsupporting
confidence: 79%
“…This is a significant result since, prior to the recent taxonomic revision of Sophora in New Zealand [ 4 , 6 ], S. chathamica was not an accepted species and S. fulvida and S. longicarinata were treated as varieties of S. microphylla [ 25 ]. In contrast, S. prostrata , with its divaricate growth habit, small and few leaflets, and resupinate flower, has long been accepted as a distinct species, and in previous genetic studies, it is one of the few species to have been distinguished [ 9 , 10 ], a result supported in this study. However, S. molloyi appeared to be similar in assignment to S. microphylla , and S. godleyi comprised individuals with a range of assignment values as well as samples that appeared to be uniquely assigned to S. godleyi (pink samples in Figure 2 ).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations